2018
DOI: 10.3139/146.111751
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of a collagen–brushite cement as a drug delivery system

Abstract: Calcium phosphate cements are known for their biocompatibility and bioactivity, which has led to a significant increase in their use. They have the advantage of being prepared as a malleable paste that sets in a few minutes and can be easily applied in bone defects. In this research work, 6 brushite cement formulations were prepared and the effect of collagen addition and the release of tetracycline were evaluated. All cements gave a malleable paste that set in 2 or 3 min, resulting in a material with pores of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
3
2
0
Order By: Relevance
“…Table 2 shows the results of the mechanical property (compression strength) evaluation. Values between 1.6 and 2.6 MPa for the compressive strength of the samples were obtained, which corresponds to what is reported in the literature for this type of cement [ 13 , 16 , 21 , 30 ].…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Table 2 shows the results of the mechanical property (compression strength) evaluation. Values between 1.6 and 2.6 MPa for the compressive strength of the samples were obtained, which corresponds to what is reported in the literature for this type of cement [ 13 , 16 , 21 , 30 ].…”
Section: Resultssupporting
confidence: 85%
“…It is also observed that the samples with sodium alginate and without the presence of tetracycline in their formulations (A2T0 and A5T0) were the ones that reached the highest values. As expected, the addition of sodium alginate increases the mechanical properties of the material; this result corresponds with the effect reported in other studies [30].…”
Section: Mechanical Propertiessupporting
confidence: 92%
See 3 more Smart Citations